Financial Planning: A Key Factor in Successful Family Business Succession in Semarang Regency, Indonesia - Elmanto Zebua; Palupiningtyas, Dyah (International Journal of Economic, Finance and Business Statistics, 2024)
This qualitative case study delves into the significance of financial planning in achieving successful family business succession in Semarang Regency, Indonesia. By conducting in-depth interviews, observations, and document analysis of 5-7 family businesses, the study investigates the current financial planning practices, the factors that influence their implementation, and the resulting impact on succession outcomes. The findings highlight that well-structured financial planning leads to a more seamless succession process and minimizes family conflicts. The study identifies several factors, including the owner's education level, available financial resources, family dynamics, and organizational culture, as key influencers in the adoption of effective financial planning strategies. The research emphasizes the crucial role of comprehensive financial planning in ensuring a successful succession and the long-term sustainability of family businesses, taking into account the local cultural context and business scale. The study also offers recommendations for optimizing financial planning strategies to support family businesses in their succession endeavors.